2002
DOI: 10.1046/j.1365-2648.2002.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing side‐effects: the clinical impact of nurse‐administered ‘side‐effect’ checklists

Abstract: The usefulness of the evaluation checklists for detecting unattended problems, in conjunction with the responses of service users, suggests that it may be clinically effective to establish procedures to systematically monitor people with serious mental illness for adverse drug reactions (ADRs). However, larger studies are needed to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 53 publications
3
58
0
Order By: Relevance
“…The Profile prompted health promotion regarding sub-optimal health behaviours, such as poor mouth care or adding salt to meals, and referrals to other professionals. Although some problems were addressed immediately, such as changes in doses of respiratory medicines, clinical gains from nurse-led medication monitoring in outpatient departments depend, in part, on participants following advice to contact other healthcare professionals [60], [61]: for example to treat suspected infections (12/26), obtain overdue vaccinations (12/26) or investigate falls (2/26). Instigation of further treatment or over-treatment would be at the discretion of professionals receiving the referrals, and not directly attributable to the Profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Profile prompted health promotion regarding sub-optimal health behaviours, such as poor mouth care or adding salt to meals, and referrals to other professionals. Although some problems were addressed immediately, such as changes in doses of respiratory medicines, clinical gains from nurse-led medication monitoring in outpatient departments depend, in part, on participants following advice to contact other healthcare professionals [60], [61]: for example to treat suspected infections (12/26), obtain overdue vaccinations (12/26) or investigate falls (2/26). Instigation of further treatment or over-treatment would be at the discretion of professionals receiving the referrals, and not directly attributable to the Profile.…”
Section: Discussionmentioning
confidence: 99%
“…Patient safety might be improved by concurrent medication monitoring using drug specific checklists [61], [80], [102][106]. The WWADR Profile helped nurses structure and prioritise care, and identify previously unsuspected problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUM is unique among these interventions as it emphasizes on the monitoring process, leveraging on the capabilities and roles of the pharmacist as the educator and advocator for appropriate medication use [33] and the nursing staff as the keen first-hand observer [34], to support the appropriate APDs by the visiting psychiatrist. While the use of the validated APP scale in the PUM form ensured the objectivity and clinical relevance of the nursing staff's monitoring and feedback, the observation-based PUM intervention enabled the nursing staff to monitor residents efficiently and overcome potential language barriers between the majority of non-English-speaking residents and nursing staff (or English-speaking residents and non-English-speaking nursing staff) when assessing BPSD changes and side effects.…”
Section: Unique Characteristics Of the Pum Interventionmentioning
confidence: 99%
“…In acute mental healthcare234 and other settings,5 we have shown that the introduction of thorough, structured checks by nurses and care staff can identify problems related to antipsychotics and prompt preventive action. We developed an intervention 67 to facilitate nurse led review of patients with serious mental illness, which pre-empted serious adverse reactions, including chest pain and pancreatitis 2.…”
mentioning
confidence: 99%